Optimalisasi Manajemen Waktu Tidur Demi Meningkatkan Produktivitas Remaja Dengan Pendekatan Kesehatan Dan Nilai-Nilai Islam - Muhammad Athaya Zain; Muhammad Irfan Hanif (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The research background indicates that modern teenagers often struggle to manage their sleep time due to academic pressures, activities, social media, and electronic devices. This threatens the quality of their sleep and has a negative impact on their health. Therefore, it is essential to emphasize the importance of healthy sleep recommendations, including the Islamic perspective, to enhance adolescent productivity. The research aims to explore the challenges of adolescent sleep and strategies to improve sleep management by integrating Islamic values. A literature review method is used to gather and analyze data from various sources. The research conclusion emphasizes the importance of sleep as a natural human need and the negative effects of sleep deprivation on the productivity, academic performance, mental health, and physical well-being of adolescents. Therefore, good sleep time management, following age-specific guidelines and Islamic values, is necessary to improve the physical and mental health and productivity of adolescents. The research implications suggest that adolescents need to adhere to age-appropriate sleep recommendations and Islamic guidelines. This will help improve academic performance, mental and physical health, and reduce stress. Effective sleep time management will contribute to achieving a balance in mental, physical, and spiritual health aspects, ultimately enhancing adolescent productivity.